Structural, Elastic, Thermodynamic and Phonon Properties of EuX3 (X=Pd, Sn and In) Intermetallic Compounds - Torrichi, M. (Algerian Journal of Research and Technology (AJRT), 2019)
The ab initio computations have been performed to examine the structural, elastic, phonon and thermodynamic properties of the rare-earth intermetallic compounds EuX3 (X=Pd, Sn and In) in AuCu3-type structure. We have performed our calculations within the generalized-gradient approximation (GGA) with ultrasoft pseudopotentials (USPP). The calculated structural parameters, such as the lattice constant, bulk modulus, its pressure derivative, cohesion energy are presented and compared with available data. In order to obtain more information about the mechanical stability we calculated second-order elastic constants, shear modulus, Young’s modulus and Poisson’s ratio. Phonon dispersion curves have been obtained using the first-principle linear-response approach of the density-functional perturbation theory. We have also performed the thermodynamic properties of EuX3 (X=Pd, Sn and In) intermetallic compounds by using quasi-harmonic approximation. The specific specific heat, internal energy, entropy and F vibration of these three intermetallic compounds are calculated and discussed.